Formation of pedagogical creativity in future primary school teachers within the higher education system - Svetlana I. Belovitskaya; Olga V. Glazyrina (Russian Journal of Education and Psychology, 2025)
The article explores the specifics of the development of pedagogical creativity in future primary school teachers. It emphasizes the importance of effectively organizing teacher training by creating pedagogical conditions within higher education that immerse students in real professional activity. Based on a theoretical analysis of the works of both Russian and international scholars, the authors identify the features of the staged immersion of students in professional practice, highlighting the distinctive characteristics of the educational process at each stage of study.